BOOSTING SPEAKING PERFORMANCE THROUGH DEBATING : STUDENTS PERCEPTION AT UDS (UMUSLIM DEBATING SOCIETY) (Survey Research): BOOSTING SPEAKING PERFORMANCE THROUGH DEBATING : STUDENTS PERCEPTION AT UDS (UMUSLIM DEBATING SOCIETY) (Survey Research) - Muthmainnah, Nafsul; misnar, Misnar (Journal of English Education and Social Science, 2021)
The problem of this research is : what are the Umuslim Debating Society’s student perception on the use of debate to boosting speaking performance. The objectives of this research is : To describe and to analyze the Umuslim Debating Society’s students perception on the use of debate to boosting speaking performance. The type of this research is a qualitative research and the methodology that used is survey research with using interview and questionnaire as an instrument. The results of this research is debate The results of this study indicate that debate can help improve students’ speaking skills because students are trained to speak a lot since they have to convey their arguments well and fluently. If they cannot speak English fluently then they will also not be able to present their arguments which is very much required in the debate. Debate also increase a lot of students’ vocabulary because students are required to speak, read and hear with many things, this is always done repeatedly so that usually when students read or hear from English websites, in the end students will get used to those vocabulary. Debate can increase students’ confidence so that the possibility of students feeling shy when speaking will not happen again when they have started arguing because when arguing they are required to convey their arguments confidently as a result of public speaking training. At the end it will also boost their speaking performance wich is very necessary for students. Debate will also help them in gaining confidency and ability to create an logic argument. Therefore, it can be one of the methods that should be used by teachers in learning English speaking classes because it can be an effective method to significantly improve students’ speaking skills.